Prevalence of Angina Pectoris and Associated Factors in the Adult Population of Brazil: National Survey of Health, 2019 - Deborah Carvalho Malta; Pedro Cisalpino Pinheiro; Nádia Machado de Vasconcelos; Sheila Rizzato Stopa; Maria Lúcia França Pontes Vieira; Paulo Andrade Lotufo
ABSTRACT: Objective: to estimate the prevalence and factors associated with angina pectoris in the Brazilian adult population and per federated units. Methods: Cross-sectional descriptive study that analyzed data from the National Survey of Health 2019 and assessed the prevalence of angina in the Brazilian population. Angina was defined as chest pain or discomfort when climbing hills or stairs, or when walking fast on flat terrain (angina I) or when walking at normal speed on flat terrain (angina II). Prevalence, crude and adjusted prevalence ratios were calculated, with a 95% confidence interval, according to sociodemographic characteristics (sex, age group, self-reported race/skin color and region of residence) and federative units. Results: The prevalence of mild angina (grade I) was 8.1% and of moderate/severe angina (grade II) was 4.5%, being both more prevalent in women (9.8 and 5.5%, respectively). The prevalence increased progressively with age and was inversely proportional to years of formal study. Grade I angina was higher in individuals self-reportedly black and residents of Sergipe (10,4%). Angina II was more prevalent in people self-reportedly brown and living in Amazonas (6.3%). Conclusion: Angina affects more than 10% of the Brazilian population aged 18 years old and more, with higher prevalence in states in the North and Northeast. This is a problem that affects the most vulnerable populations unequally, which places coronary heart disease as a public health problem and points to the need to think about public policies aimed at these strata of the population.